2021
DOI: 10.1101/2021.03.01.433441
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Top-down control of hippocampal signal-to-noise by prefrontal long-range inhibition

Abstract: The prefrontal cortex (PFC) is postulated to exert 'top-down control' by modulating information processing throughout the brain to promote specific actions based on current goals. However, the pathways mediating top-down control remain poorly understood. In particular, knowledge about direct prefrontal connections that might facilitate top-down prefrontal control of information processing in the hippocampus remains sparse. Here we describe novel monosynaptic long-range GABAergic projections from PFC to hippoca… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 80 publications
0
10
1
Order By: Relevance
“…In particular whether a role in motivated behaviour and place preference was specific to BA input, or due to the dorso-ventral location of this input in hippocampus. Interestingly, long range inhibition from entorhinal cortex, septum and PFC all preferentially target interneurons and avoid pyramidal neurons (Basu et al, 2016;Malik et al, 2021;Melzer et al, 2012;Schlesiger et al, 2021). In contrast our data shows that BA long range inhibition connects with both interneurons and pyramidal neurons (Figure 3), similar to that seen in long range inhibitory projections from BA to PFC (Seo et al, 2016).…”
Section: Discussioncontrasting
(Expert classified)
See 2 more Smart Citations
“…In particular whether a role in motivated behaviour and place preference was specific to BA input, or due to the dorso-ventral location of this input in hippocampus. Interestingly, long range inhibition from entorhinal cortex, septum and PFC all preferentially target interneurons and avoid pyramidal neurons (Basu et al, 2016;Malik et al, 2021;Melzer et al, 2012;Schlesiger et al, 2021). In contrast our data shows that BA long range inhibition connects with both interneurons and pyramidal neurons (Figure 3), similar to that seen in long range inhibitory projections from BA to PFC (Seo et al, 2016).…”
Section: Discussioncontrasting
(Expert classified)
“…For example, functional inhibitory projections from PFC to NAc (A. T. Lee et al, 2014), and BA to PFC (Seo et al, 2016) have both been shown to modulate value-based and reward behaviour, including the support of real time place preference and aversion. The hippocampus also receives long range inhibitory input from numerous regions including entorhinal cortex (Basu et al, 2016; Melzer et al, 2012), septum (Schlesiger et al, 2021) and PFC (Malik et al, 2021). While these studies focussed on dorsal hippocampal circuitry and a role for these projections in memory and navigation, due to the known dichotomy between dorsal and ventral hippocampal function (Fanselow and Dong, 2010; Strange et al, 2014), it would be interesting to investigate the presence and function of such long range inhibitory projections into vH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A potential mechanism for the increased inhibition is suggested by a recent report describing a powerful direct top-down control of hippocampus by prefrontal cortex, via a specific subset of inhibitory long-range projection neurons. These projections preferentially inhibit vasoactive intestinal polypeptide expressing interneurons in the hippocampus, which result in disinhibition of hippocampal interneurons mediating feed-forward inhibition, leading to a net increase in inhibitory drive onto hippocampal pyramidal cells (Malik et al, 2021). The connection between prefrontal cortex and hippocampus is interesting in light of the finding that prefrontal cortex neurons of mice can form distinct representations of urine pooled from either several male or female conspecifics, although whether prefrontal cortex can encode representations of specific individual social odors remains to be determined (Levy et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The HC, a core memory structure in the brain, has strong projections to mPFC with very few direct return projections from mPFC. In fact, return projections were only recently described by Malik et al, (2021) as a population of direct GABAergic projections from mPFC to inhibitory vasoactive intestinal polypeptide (VIP) interneurons in dorsal HC. Most mPFC communication with HC is polysynaptic.…”
Section: Introductionmentioning
confidence: 99%